(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
On 20 March 2021, Turkey withdrew from the Council of Europe Convention on Preventing and Combating Violence against Women and Domestic Violence (‘Istanbul Convention’) with a presidential decree. President Erdoğan’s decision and the way in which it was carried out has led to great discontent both within the country and on the international scenario. The main aim of this analysis is to explore the meaning, impact and aftermath of the Turkish government’s decision. The article is divided into two parts: the first part analyses the scope and purposes of the Istanbul Convention, and the second part explores Turkey’s increasing authoritarianism over the last decade, which offers the framework to interpret its decision to withdraw.